2008
DOI: 10.1007/s15010-008-7377-8
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Local Antibiotic Management Program on Antibiotic Use in a Tertiary Intensive Care Unit in Hungary

Abstract: This study has confirmed that establishing a targeted LAMP, based on close co-operation between intensive care physicians and infectious disease specialists together with a restricted prescribing authority, can reduce the use of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
0
29
1
Order By: Relevance
“…Stratifying the studies per hospital setting, we found that studies conducted in medical wards achieved an antimicrobial reduction of Ϫ12.1% (95% CI ϭ Ϫ19.9 to Ϫ4.3%, 2 ϭ 0.00) (37,40,43,51), whereas the studies conducted in an ICU reached a decrease of Ϫ39.5% (95% CI ϭ Ϫ72.5 to Ϫ6.4, 2 ϭ 0.13) (31,33,45,47), with no small-study effect (Egger's bias ϭ Ϫ0.2, P ϭ 0.823) based on four studies. This difference between medical wards and the critical care setting was Ϫ27% and was statistically significant (95% CI ϭ Ϫ72.3 to Ϫ5.5) (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Stratifying the studies per hospital setting, we found that studies conducted in medical wards achieved an antimicrobial reduction of Ϫ12.1% (95% CI ϭ Ϫ19.9 to Ϫ4.3%, 2 ϭ 0.00) (37,40,43,51), whereas the studies conducted in an ICU reached a decrease of Ϫ39.5% (95% CI ϭ Ϫ72.5 to Ϫ6.4, 2 ϭ 0.13) (31,33,45,47), with no small-study effect (Egger's bias ϭ Ϫ0.2, P ϭ 0.823) based on four studies. This difference between medical wards and the critical care setting was Ϫ27% and was statistically significant (95% CI ϭ Ϫ72.3 to Ϫ5.5) (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Studies conducted in the United States (30,(34)(35)(36) and in Europe (29,33,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) reported the highest pooled decrease in antimicrobial consumption after the implementation of ASP (Ϫ19.9% [95% CI ϭ Ϫ27.7 to Ϫ12.1, 2 ϭ 0.00] and Ϫ20.9% [95% CI ϭ Ϫ30.5 to Ϫ15, 2 ϭ 0.05], respectively), whereas studies in Asia reported a reduction of Ϫ16% (95% CI ϭ Ϫ36.5 to Ϫ5.3], 2 ϭ 0.11) (28, 31, 32, 47-52) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations